Analysis Of the Financial and Non-Financial Performance of the Bogor District Office (A Case Study of The Public Works And Spatial Planning Office) - Novianisa, Rany; Pahala, Indra; Ulupui, I Gusti Ketut Agung (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
This study aims to analyze the financial and non-financial performance of the Bogor District Office, especially in terms of public works and spatial planning. This method is applied to measure the financial performance using the independence ratio, activity ratio, efficiency ratio, and growth ratio and measure the non-financial performance of the Office using the Community Satisfaction Survey based on the Minister of State Apparatus Empowerment and Bureaucratic Reform RT Regulation Number 14 of 2017. Through a case study approach, data will be collected and analyzed from various sources, including financial data and community satisfaction surveys. The method used in this research is descriptive analysis.